KONSENTRASI DAN KUALITAS PERGURUAN TINGGI SWASTA DI KOPERTIS WILAYAH XII - Elia Radianta (Jurnal Kependidikan, 2008)
In an effort to improve the strength of the nation to competethrough higher education, this study was taken with an objective toknow the concentration and quality of private universities under theRegion XII Private University Coordinative Body using (1)Geographical Information System Analysis, (2) Table Analysis, and (3)Logit Model Analysis. It was found that, of the 75 private universities inthe region, 48% were geographically concentrated in Papua Province, 21.33% in Maluku, 17.33% in West Papua, and 13.33% in North Maluku. It was suggested that (1) the government attention should bedirected either through human resources improvement or localeconomic development; (2) the government commitment was needed toadvocate the human resources in each region to be the future leaders inimproving the quality of private universities to fulfil the expectation ofHELTS; and (3) the institutional capacity improvement needed to beextended